Perbedaan Kebutuhan Kalori, Status Gizi, Dan Kebiasaan Sarapan Pada Mahasiswa Keperawatan - Hilda Mazarina Devi; Yanti Rosdiana; Ani Sutriningsih (Indonesian Journal of Health Research, 2022)
Introduction. Every human being, including students, has five basic needs including physiological nutritional needs. This study aims to determine the calorie needs, nutritional status and breakfast habits of nursing students to then be compared based on gender differences. Methods. The research method used is a cross-sectional method with a descriptive analytical approach. Data were obtained from 72 nursing students who took part in the FIKes Nursing Study Program FIKes University Tribhuwana Tunggadewi lecture on Fulfillment of Basic Human Needs in 2021/2022 using total sampling. Data analysis using Pearson Chi-quare and Fisher Exact. Results. The results showed that there was a significant difference between male and female students in calorie needs. Meanwhile, there was no significant difference in nutritional status and breakfast habits. A total of 66 students have a thin-normal nutritional status, with 46 people having a calorie requirement of > 1801 kcal/day. Conclusion. Maintaining the fulfillment of nutrition properly and proportionally according to the difference needs between men and women is highly recommended to preserve the current health status and gaining a quality in old age.